Effects of different exercise intensities in the morning on football performance components in the afternoon - Oh, S. H.; Mierau, A.; Thevis, M.; Thomas, A.; Schneider, C.; Ferrauti, A. (German Journal of Exercise and Sport Research, 2018)
The aim of this study was to investigate the effect of two different exercise interventions in the morning on football-specific components of performance in the afternoon under conditions simulating a competition day. In the morning on 3 experimental days, 12 football players (age 24.1?±?5.5 years) completed three different preload interventions that were applied in a counter-balanced order: (1) no intervention (NI); (2) moderate-intensive exercise (MI); and (3) high-intensive exercise (HI). The subjects performed the preload exercises, consisting of a small-sided game and repeated maximal sprints, from 10:00-11:00 a.m. At 3:00 p.m., the Bangsbo test (BT) was applied to examine the effects of the different morning interventions on football-specific endurance capacity. The results showed that the HI led to significantly higher blood-lactate concentrations (moderate to very large effect) and heart rates (very large to extremely large effect) compared to the MI. In addition, there was a significant measurement?×?intervention effect on concentrations of adrenalin and noradrenalin in the urine, which reached higher values immediately after the HI (very large effect) and MI (moderate effect) compared to NI. All effects disappeared by the time of the BT in the afternoon. During all trials, after the preload intervention, reaction time and critical flicker fusion frequency increased significantly compared to the baseline morning values (reaction time: small; critical flicker fusion: trivial to small effect), but no measurement?×?intervention interaction was found. During the BT, the mean total distance covered (trivial to small effect) and the pacing pattern did not differ significantly among the trials despite numerous small individual effects. We conclude that exercise interventions of various intensities in the morning have no general effect on football-specific components of performance in the afternoon despite significant metabolic, endocrinological and cognitive short-term effects. Coaches should consider individual preferences when prescribing competition-day procedures. Ziel der Studie war es, den Effekt zweier unterschiedlicher Übungsinterventionen am Morgen auf fußballspezifische Leistungskomponenten am Nachmittag unter simulierten Bedingungen eines Wettkampftags zu untersuchen. An 3 Versuchstagen absolvierten 12 Fußballer (Alter 24,1?±?5,5 Jahre) morgens 3 verschiedene Vorlastinterventionen, die in einer ausgleichenden Reihenfolge eingesetzt wurden: 1. keine Intervention (KI); 2. mäßig intensive Übung (MI) und 3. hoch intensive Übung (HI). Die Studienteilnehmer führten die Vorlastübungen, die ein Kleinfeldspiel und wiederholte Maximalsprints umfassten, von 10:00 bis 11:00 Uhr durch. Um 15:00 Uhr erfolgte der Bangsbo-Test (BT), um die Effekte der verschiedenen morgendlichen Interventionen auf die fußballspezifische Ausdauerleistungsfähigkeit zu untersuchen. Im Ergebnis führte die HI verglichen mit der MI zu signifikant höheren Blutlaktatkonzentrationen (mäßiger bis sehr großer Effekt) und Herzfrequenzwerten (sehr großer bis extrem großer Effekt). Darüber hinaus fand sich ein signifikanter Messungs-Interventions-Effekt auf die Konzentrationen von Adrenalin und Noradrenalin im Urin, die unmittelbar nach HI (sehr großer Effekt) und MI (mäßiger Effekt) höhere Werte erreichten als nach KI. Zum Zeitpunkt des BT am Nachmittag war keiner der Effekte mehr nachweisbar. Bei allen Studieninterventionen erhöhten sich die Reaktionszeit und Flimmerverschmelzungsfrequenz nach der Vorlastintervention signifikant im Vergleich zu den Werten der morgendlichen Ausgangsmessung (Reaktionszeit: kleiner Effekt; Flimmerverschmelzungsfrequenz: unwesentlicher bis kleiner Effekt), es fand sich aber keine Messungs-Interventions-Interaktion. Im BT unterschieden sich die mittlere zurückgelegte Gesamtstrecke (unwesentlicher bis kleiner Effekt) und das Geschwindigkeitsmuster nicht signifikant zwischen den Studieninterventionen, trotz einer Vielzahl kleiner individueller Effekte. Daraus lässt sich schließen, dass morgendliche Übungsinterventionen verschiedener Intensitäten keinen allgemeinen Effekt auf fußballspezifische Leistungskomponenten am Nachmittag haben, trotz signifikanter metabolischer, endokrinologischer und kognitiver Kurzzeiteffekte. Wenn Trainer die Abläufe für den Wettkampftag vorgeben, sollten sie individuelle Vorlieben berücksichtigen.